EKSISTENSI KAMPUNG LAMA MELALUI KEARIFAN LOKAL DI KAMPUNG BUSTAMAN SEMARANG - Annisa Mu’awanah Sukmawati; Nany Yuliastuti (Diponegoro University, 2016)
Kampung Bustaman is an old kampong in the center of Semarang City that still can exist. The research aims to find the factors that influence the existence of Kampung Bustaman and to give the strategy to strengthen the existence of Kampung Bustaman through its local wisdom. The research was conducted using qualitative research with case study approach. The sampling technique used is snowball sampling. Analysis was conducted using descriptive qualitative analysis which aims to provide in-depth descriptions of the conditions of existence of Kampung Bustaman through local wisdom. The results shows that Kampong Bustaman still able to exist in the middle of urban development using local wisdom. Local wisdom has manifested in the daily life, consist of physical artifacts, economic activity, religious traditions, and social life. Local wisdom in the form of economic activity has been the spirit for the Bustaman’s occupants. The existence of the diversification activities related to the goats and culinary business that was involved Bustaman’s occupants were able to enliven kampung space condition and the most of Bustaman’s occupants. Local wisdom possessed also continued to strengthen in line with the times and the increasing need for people who require the existence of space and the role of the various parties to reinforce it.